Ecological and genetic assessment of the consequences of radiation influence on contaminated areas - A. B. Bigaliev; K. Z. Shalabaeva; B. E. Shimshikov; S. S. Kobegenova; L. M. Adilova; A. N. Kozhakhmetova; S. Sharakhmetov; M. N. Burkhanova (Вавиловский журнал генетики и селекции)
The objects of study are the territory of the districts of the West Kazakhstan region of the Republic of Kazakhstan adjacent to the Kapustin Yar test site: Bokeyordinsky, Zhangalinsky, Zhanibeksky, Kaztalovsky, Akzhayiksky and Syrymsky. The purpose of the work is to conduct a radioecological survey of contaminated areas and to study the content of pollutants in environmental objects, biota (rodents, fish and biosubstrates of domestic animals) by physicochemical methods to assess the risk of the landfill’s impact on biota and humans. This paper presents the results of expeditionary and laboratory research on the pollution of environmental objects in the areas adjacent to the landfill. Indicators of the gamma-survey of the levels of radiation background of the surveyed territories as wellas data on pollution of soil, surface and ground waters, dominant forms of plants, biosubstrates (hair of domestic animals: camel, horse, cow) are given. The generally accepted research methods were used: standard sampling me thods, radiological, atomic adsorption spectrophotometry, cytogenetic (micronucleus) method. A reconnaissance and radioecological examination of environmental objects was carried out using analytical methods, which made it possible to determine the quantitative content of toxic components, the content of priority pollutants and radioactive isotopes. It has been established that the values of the volumetric activity of natural and man-made radionuclides in soil samples, drinking water and biosubstrates (pet hair, human peripheral blood samples) from settlements correspond to the value of the control level for this region. The measurements of radiation activity by gamma radiation showed that along the perimeter of the surveyed territory of the test site and in nearby settlements the radiation level is in the range of 0.06–0.014 μSv/h. A slight excess of the level of radioactivity persists in the area near the fall of missiles in the Bokeyordin region. The investigated regions are characterized by an insignificant level of background radiation, the average DER value for the regions as a whole is 0.14 μSv/h. The absolute maximum, 0.73 μSv/h, was recorded at the points of missile impact in the Kaztal region.